Microencapsulation, Chemical Characterization, and Antimicrobial Activity of Mexican (Lippia graveolens H.B.K.) and European (Origanum vulgare L.) Oregano Essential Oils - Elvia Hernández-Hernández; Carlos Regalado-González; Pedro Vázquez-Landaverde; Isabel Guerrero-Legarreta; Blanca E. García-Almendárez (The Scientific World Journal)
The effect of solvent polarity (methanol and pentane) on the chemical composition of hydrodistilled essential oils (EO’s) of Lippia graveolens H.B.K. (MXO) and Origanum vulgare L. (EUO) was studied by GC-MS. Composition of modified starch microencapsulated EO’s was conducted by headspace-solid-phase microextraction (HS-SPME). The antimicrobial activity of free and microencapsulated EO’s was evaluated. They were tested against Salmonella sp., Brochothrix thermosphacta, Pseudomonas fragi, Lactobacillus plantarum, and Micrococcus luteus. Thymol and carvacrol were among the main components of EO’s and their free and microencapsulated inhibitory activity was tested against M. luteus, showing an additive combined effect. Chemical composition of EO’s varied according to the solvent used for GC analysis and to volatile fraction as evaluated by HS-SPME. Thymol (both solvents) was the main component in essential oil of MXO, while carvacrol was the main component of the volatile fraction. EUO showed α-pinene (methanol) and γ-terpinene (pentane) as major constituents, the latter being the main component of the volatile fraction. EO’s showed good stability after 3 months storage at 4°C, where antimicrobial activity of microencapsulated EO’s remained the same, while free EO’s decreased 41% (MXO) and 67% (EUO) from initial activity. Microencapsulation retains most antimicrobial activity and improves stability of EO’s from oregano.